PENGARUH MODEL PEMBELAJARAN BEYOND CENTERS AND CIRCLE TIMES (BCCT) DAN KEMANDIRIAN TERHADAP KREATIVITAS - RUQOYAH, ADIANTI (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
This study aims to identify and analyze the influence of the learning model beyondcenters and circle times (BCCT) and the child's independence against group B TK creativityAmanah West Jakarta. A sample of 34 children using Random Sampling technique Stratifeid. Theinstrument uses a questionnaire of independence and creativity test tool. Testing is done with thecorrelation validity and reliability testing point biserial Kuder- Richardson reliability coefficients20. In this study hypothesis test conducted with hotelling t multivariate analysis, independent t testand chi square analysis. The results showed: 1) there are differences in child outcomes that havelow creativity among groups and non BCCT bct (T2hitung (36.6)> C2 (11.83)). 2) there aredifferences in the results of children who have high creativity among groups and non BCCT BCCT(T2hitung (36.6)> C2 (11:45)). 3) There is an interaction effect BCCT learning model and theindependence of thecreativity of children (p-value 0.013). 4) There are differences in the results ofchildren who have low self-reliance among groups and non BCCT BCCT (t2hitung (95.51)> c2(12:33)). 5) there are differences in the results of children who have high self-reliance amonggroups and non BCCT BCCT (t2hitung (82.47)> c2 (12:33).